The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s004200000163
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruptors: update on xenoestrogens

Abstract: Endocrine disruptors and their possible impact on human and animal health have become a topic of discussion and an area of active research in toxicology. A focus has been on xenoestrogens, i.e., environmental chemicals with estrogenic activity. In principle, there is agreement that such compounds, in high doses, may cause developmental, reproductive and tumorigenic effects ("hazard"). A matter of controversy is the question of risks associated with xenoestrogens under realistic (low) exposure scenarios; this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…Based upon numerous previous studies, xenoestrogens, also called "environmental estrogens or hormones" or "Endocrine Disrupting Compounds (EDC)", are considered as serious environmental hazards that have hormone disruptive effects on human and wildlife health [5,6]. Studies have found that fetuses and young children exposed to BPA are at risk for secondary sexual developmental changes, brain and behavior changes and immune disorders [7].…”
Section: Environmental Estrogen-biphenol a (Bpa)mentioning
confidence: 99%
“…Based upon numerous previous studies, xenoestrogens, also called "environmental estrogens or hormones" or "Endocrine Disrupting Compounds (EDC)", are considered as serious environmental hazards that have hormone disruptive effects on human and wildlife health [5,6]. Studies have found that fetuses and young children exposed to BPA are at risk for secondary sexual developmental changes, brain and behavior changes and immune disorders [7].…”
Section: Environmental Estrogen-biphenol a (Bpa)mentioning
confidence: 99%
“…The availability of funds in areas of political preference may have a higher impact on the choice of a particular research field than scientific considerations. A now classical example for such a development is the global wave of publications on ''endocrine disruptors'' (Degen and Bolt 2000).…”
mentioning
confidence: 99%
“…Xenoestrogens as environmental contaminants have sparked much debate as a public health concern, because significant levels are present in the environment (Degen and Bolt, 2000). The industrial chemical bisphenol A (BPA; used to make polycarbonate plastics and epoxy resins), naturally occurring plant estrogens (e.g., zearalenone), and the potent synthetic pharmaceutical estrogen diethylstilbestrol (DES) are some examples of the more prevalent environmental xenoestrogens of toxicological interest (Degen and Bolt, 2000;Juberg, 2000;Safe, 2000).…”
mentioning
confidence: 99%
“…The industrial chemical bisphenol A (BPA; used to make polycarbonate plastics and epoxy resins), naturally occurring plant estrogens (e.g., zearalenone), and the potent synthetic pharmaceutical estrogen diethylstilbestrol (DES) are some examples of the more prevalent environmental xenoestrogens of toxicological interest (Degen and Bolt, 2000;Juberg, 2000;Safe, 2000). Although the potential hazard to human health from exposure to environmental xenoestrogens has not been conclusively determined (Degen and Bolt, 2000;Juberg, 2000;Safe, 2000), significant reproductive and associated anomalies in wildlife have been attributed to their exposure to xenoestrogens (Juberg, 2000), raising a significant health concern for humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation